Differential brain volume between obese and underweight cognitively normal older adults with frailty in the JPSC-AD - Naoki Ishizuka; Hiroshi Akasaka; Mitsunobu Sato; Yuriko Sato; Kazuki Hosokawa; Junko Takahashi; Hisashi Yonezawa; Yasuo Terayama; Tomoyuki Ohara; Takanori Honda; Mao Shibata; Jun Hata; et al. (Scientific Reports)
Abstract Frailty is common in older adults; however, the central nervous system mechanisms underlying the differences between obesity and underweight remain unclear. This study investigated brain volume in frail, cognitively normal, community-dwelling older adults across three body mass index (BMI) groups: low (< 18.5), intermediate (18.5–24.9), and high (≥  25.0). Whole and regional brain volumes were measured and analyzed. Among 3,627 participants, those in the high BMI group (n = 1,134) had significantly lower multivariate-adjusted total brain volume (66.8% vs. 67.3%, p < 0.001) and gray matter volume (36.1% vs. 36.6%, p < 0.001) than participants in the intermediate BMI group (n = 2,274). Volume differences were observed in the frontal, parietal, temporal, and cingulate cortices, as well as the hippocampal gyrus; amygdala; superior, middle, and inferior temporal gyri; temporal pole; parahippocampal gyrus; and cuneus. Compared with the intermediate BMI group, the low BMI group (n = 219) presented a significantly lower volume in the middle temporal gyrus (1.91% vs. 1.95%, p = 0.008). These findings indicate that older adults with frailty experience differences in brain volume, with atrophy patterns differing based on BMI. Therefore, the central nervous system dysfunction may play a role in the mechanisms underlying frailty.